(untitled) (Revista Sistemas de Producción Agroecológicos, 2010)
This investigation evaluated the silage of Erythrina glauca forage in its nutritional quality, to be used later on in the animal feeding of in Colombia. The Erythrina glauca silage, was pack in silage bag was added to forage three levels of molasses (10%, 15% and 20%), besides, was added 3% of flour of rice by treatment, being the other half of the forage without flour, the silaje, was analyzed in four times of maturation: 0, 30, 60 y 90 days; with three repetitions each one. The trial was randomized completely to the chance with a factorial arrangement of 3x4x2, being respectively for treatments, and times of maduration and addition of flour of rice: It was used variance analysis and test of Tukey. The evaluated variables were: Dry matter, protein, raw fiber, fat, non-nitrogenaus extract, ash, the fiber in the neuter detergent (NFD), fiber in the acid detergent (AFD) and degradation in the rumen of the dry matter (DDM). The content of matter of the silage increased (P<0.05) when the levels of molasses were increased and flour of rice was added, while the time of maturation did not influence (P>0.05) on the DM content. The protein content decreased (P<0.05) as it increases the time of maturation, but it is increased (P<0.05) when flour of rice is added. The raw fiber, the NFD and the AFD decreased (P<0.05) as the time of maturation was increased. The opposite happened to the DDM at the 72 hours, which was increased (P<0.05) as it increased the time of maturation. The DDM in the different hours of degradation was minimum, being observed an alike result (P>0.05) in each one of the evaluated hours (6, 12, 24, 48 and 72) The DDM was quick in the first 6 hours, until 39%. The increment in the following hours was: 2%, 8%, 11% and 13,7%, respectively, that which indicated that the degradation was slow after the 6 hours until the 72 hours, the fat and ashy didn’t affect any treatment. Was concluded that the raw fiber, the NFD, AFD were affected the fermentation of the microorganisms, since they break the cellular walls, causing a decrease, that which allows a bigger degradation in the rumen.